The Importance of Complexity Analysis in Information Systems - Ibl, Martin; Svoboda, Ondřej; Pařízek, Vlastimil (International Business Information Management Association-IBIMA, 2018)
With the development of new technologies and the growing tendency to gather more information, the issue of system complexity is becoming more and more relevant. Increasing complexity in the information system raises a number of problems, which in many cases can be prevented. These issues are mainly propagated in system properties such as readability, scalability, maintainability, sustainability, easiness of implementation, and many others. All these properties affect the general user friendliness and overall trust in the system. For these reasons, it is necessary to have a comprehensive view of complexity of the information system in the different phases of its life cycle. This paper deals with the complexity analysis of information systems, its causes and implications for users and organizations. The aim of this paper is to summarize ways of measuring complexity in different phases of its life cycle and different content dimensions of the information system. Selected complexity analysis is then showcased on a case study of a privately implemented real-world system. Finally, the obtained results of the analysis are evaluated and discussed.
Význam analýzy komplexity v informačních systémech
Keywords: Complexity; Information Systems; Analysis of Complexity; Life Cycle